Improving Agricultural Productivity and Market Efficiency in Latin America and the Caribbean: How ICTs can make a Difference? - Goyal, Aparajita; GonzÃ¡lez-Velosa, Carolina (Journal of Reviews on Global Economics, 2013)
Abstract: The rapid dissemination of ICTs in rural areas in LAC has been received with a lot of optimism, as these technologies are thought to be potentially effective tools of agricultural development. However, rigorous analyses of the impacts of ICTs on agriculture are still very scarce and lag behind the rapid penetration of these technologies. This paper is the first attempt to summarize recent findings from some of the few academic studies addressing this topic and complementing this analysis with anecdotal evidence and findings from case studies. Overall, the available evidence indicates that ICTs can play a major role in promoting agricultural productivity and rural development in LAC. By closing information gaps and reducing transaction costs, ICTs can improve the opportunities of farmers in agricultural markets and empower smallholders. ICTs can also foster productivity by facilitating the dissemination of technological knowledge and expand the access to financial and public services among the rural population by making service provision more affordable. Nonetheless, to the extent that the effective provision of ICTs has certain minimum requirements in terms of human and physical capital, many agricultural economies will be unable to reap the full benefits of these technologies.